Proposed integrated hazardous waste management facility for National Capital Region, Philippines - Doctor, Diosdado C. (1999, 1999)
Disposal of hazardous waste in the Philippine is regulated by Republic Act 6960, otherwise known as Toxic Substances, Hazardous Wastes and Nuclear Waste Control Act of 1990. The Department of Environment and Natural Resources (DENR), being one of the implementing agencies however has failed to fully implement the law. One of the reasons is the absence of a hazardous waste management facility to recycle, treat and dispose hazardous waste. A study was conducted to determine what facilities and corresponding capacities should an integrated hazardous waste management facility must have to recycle, treat (including thermal) and dispose the waste generated in National Capital Region (NCR).
Potential waste generators were identified, screened, and plotted in a map to determine their location and concentration. The quantity of hazardous waste per category were estimated, following the World Bank's proposed classification. Candidate sites in National Capital Region were identified and assessed following mostly the site selection criteria for a secure landfill. A conceptual layout of the proposed integrated facility was developed taking into consideration the physical characteristic of the site. Waste available for recycling, treatment and disposal were estimated and used as basis in determining the capability of the. Lastly, health risk associated with the siting of the integrated facility at the selected site was quantified using the quantitative risk assessment methodology. Based on the study, around 4,290.23 tons of hazardous waste are available for land disposal, 198.2 tons for recycling, 2,496.63 for treatment and 4,898.15 tons for incineration. The health risk of siting the facility for worst case scenario is both above the acceptable limit of 1 and 10^-4 and 10^-6 for non-carcinogenic and carcinogenic risk respectively.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Hazardous wastes -- Management. -- Philippines -- Manila Metropolitan Area; Hazardous wastes -- Risk assessment -- Philippines -- Manila Metropolitan Area